Adjusting to new employment landscapes: Consequences of precarious employment for young Australians. (June 2019) - Chesters, Jenny; Cuervo, Hernan
As economies transition from industrial to post-industrial, the types of jobs available and employment conditions change. Research indicates that youth employment has been negatively impacted by these changes. For young people seeking to enter the labour market, particularly those combining employment and study, precarious employment has become the norm. However, precarious employment is, for many, no longer a stepping stone on the path to permanent employment. Many young Australians, even those with higher education qualifications, experience prolonged periods of precarious employment. To examine how new employment landscapes are experienced by young workers, we conduct analysis of data collected by the Life Pattern Project, a longitudinal mixed-methods study. Our results show that precarious employment is related to lower levels of job satisfaction and autonomy in young adulthood. JEL Codes: J20, J28, J41